Faktor-Faktor yang Mempengaruhi Minat Perilaku Menggunakan Sistem Informasi Akuntasi Berbasis E-Commerce(Studi Kasus Pada Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta Pada Tahun Angkatan 2012 - 2016 ) - Novitasari, Rizky (2016)
The purpose of this study was to examine the factors that affect interests of behavior using accounting information system based on e-commerce. Reseacrh conducted at faculty of economics and business University Muhammadiyah Surakarta, besed on purposive sampling method, obtained a sample of 75 respondents. Data were collected using a questionnaire, after data is collected and data were analyzed by using multiple regression. Reseach shows that attitude subjective norm and perceived usefulness behaviors affect interest based system using e-commerce, while control behavior and ease of usability perception of no effect use of behavioral based e-commerce system. Keywords: e-commerce, subjective norm, perceived usefulness, perceived behavioral control.